2012
DOI: 10.5194/angeo-30-325-2012
|View full text |Cite
|
Sign up to set email alerts
|

3-D mesoscale MHD simulations of magnetospheric cusp-like configurations: cusp diamagnetic cavities and boundary structure

Abstract: Abstract. We present results from mesoscale simulations of the magnetospheric cusp region for both strongly northward and strongly southward interplanetary magnetic field (IMF). Simulation results indicate an extended region of depressed magnetic field and strongly enhanced plasma β which exhibits a strong dependence on IMF orientation. These structures correspond to the Cusp Diamagnetic Cavities (CDC's). The typical features of these CDC's are generally well reproduced by the simulation. The inner boundaries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 51 publications
(82 reference statements)
2
18
0
Order By: Relevance
“…However the total pressure is still lower than outside of the cavity (i). Reduced magnetic pressure, balanced by the increased thermal pressure is a typical signature of the diamagnetic cusp cavities created by reconnection in MHD (Adamson et al, ). Here the plasma pressure calculation does not include the high‐energy particles, which is why the plasma pressure does not balance the magnetic pressure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However the total pressure is still lower than outside of the cavity (i). Reduced magnetic pressure, balanced by the increased thermal pressure is a typical signature of the diamagnetic cusp cavities created by reconnection in MHD (Adamson et al, ). Here the plasma pressure calculation does not include the high‐energy particles, which is why the plasma pressure does not balance the magnetic pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 shows the plasma and field properties of the dayside magnetosphere at 09:24 UT from high-resolution MHD global simulation results, with the MMS1 location projected in each plane as well as the cartoon of the expected DMC locations based on the maximum shear of the draped IMF field around the geomagnetic field in the vicinity of the cusps. The DMCs are directly generated by reconnection in maximum magnetic shear regions in a similar manner described by Nykyri, Otto, Adamson, Dougal, and Mumme (2011) and Adamson et al (2011Adamson et al ( , 2012. These cavities are indicated by a strongly enhanced plasma beta (color scale is saturated at beta = 38 in order to better see the northern hemisphere DMC in the same plane) tailward of the MMS at x = 5 R E (panel a) in the expected regions in Southern (region iv in panels b and g) and Northern Hemispheres (region iv in panels c and h).…”
Section: Mms Observationsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the differing spacecraft velocities at high altitudes (∼10 R E ) affect the observations; Clusters larger velocity (than Polar) results in a smoothing effect of the observed diamagnetic depression, and therefore, it is only measured during enhanced (>2 nPa) solar wind dynamic pressures [Nykyri et al, 2011b]. Modeling by Adamson et al [2011Adamson et al [ , 2012 showed that the location and size of the cusp diamagnetic depression is strongly dependent on the IMF orientation, and that it is mainly structured by reconnection processes.…”
Section: 1002/2016ja023738mentioning
confidence: 99%
“…The diamagnetic cavity in the high‐latitude cusp region is also thought to be a possible source of energetic ions in the dayside magnetosphere and near‐Earth plasma sheet [e.g., Chen and Fritz , ; Fritz et al , ; Fritz et al , ]. The diamagnetic cavity is a region with enhanced plasma pressure and decreased magnetic field strengths formed by the magnetic reconnection in the high‐latitude magnetopause [e.g., Nykyri et al , , Adamson et al ., ]. This region is able to trap charged particles.…”
Section: Introductionmentioning
confidence: 99%